2022
DOI: 10.1152/ajpcell.00091.2022
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in IL-10’s anti-inflammatory function: greater STAT3 activation and stronger inhibition of TNF-α production in male blood leukocytes ex vivo

Abstract: Interleukin-10 (IL-10) inhibits pro-inflammatory cytokine production in blood leukocytes - an effect mediated by signal transducer and activator of transcription 3 (STAT3) activation. To examine potential sex-based differences in IL-10's anti-inflammatory function, we treated whole blood from healthy males and females (n=16 each; age: 28±6 years; body mass index: 23.5±2.3 kg/m2) with increasing concentrations of IL-10 (1-100 ng/mL) and quantified changes in phosphorylated STAT3 (pSTAT3) in CD14+ monocytes and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…Our current study confirms the increased IL-10 levels in RA cases on a systemic level. We should note that we limited our study to women in accordance with the known prevalence of RA among women, more than 3 folds, previously reported sex differences in IL-10 production and its anti-inflammatory properties [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our current study confirms the increased IL-10 levels in RA cases on a systemic level. We should note that we limited our study to women in accordance with the known prevalence of RA among women, more than 3 folds, previously reported sex differences in IL-10 production and its anti-inflammatory properties [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…In females, an increase in IL-4 was accompanied by a decrease in IL-10, while a reduction in IL-4 in males was accompanied by a 6-fold increase in IL-10. Interestingly, sexual dimorphism was recently described for IL-10's anti-inflammatory action toward leukocytes, and for IL-4-induced monocyte polarization (24,25). It is possible that the contrasting plasma cytokine responses we observed reflect differences in the cytokine responsiveness of leukocytes in males and females, and that this may underlie subtle changes in the pattern of inflammatory cell mobilization and recruitment to the site of injury.…”
Section: Systemic Inflammatory Responsementioning
confidence: 97%
“…Therefore, reducing levels of inflammatory cytokines is an effective strategy for treating PF. IL-10 exerts anti-inflammatory effects by inhibiting TNF-α production at the transcriptional level ( Islam et al, 2022 ). Studies have shown that MMDD can reduce alveolar inflammation and PF in rats, potentially through the decrease in IL-10 expression and inhibition of lung TNF-α, transforming growth factor-β1 (TGF-β1), platelet-derived factor (PDGF), and connective tissue growth factor (CTGF) ( Du, 2015 ).…”
Section: Mechanism Of Mmdd In the Treatment Of Pfmentioning
confidence: 99%